Relationship between HPV and HIV. Prevalence, molecular mechanisms and screening of HPV among HIV infected women - Katarzyna Kosz; Martyna Zielińska; Aleksaandra Kuchnicka; Natalia Zarankiewicz; Bogumiła Ciseł (Kazimierz Wielki University, 2020)
Introduction: Human papillomavirus (HPV) and human immunodeficiency virus (HIV) are the most common sexually transmitted infections (STI) globally. According to the World Health Organisation (WHO) there are around 17.4 million women living with HIV and over 290 million HPV infected women worldwide. Purpose: This review is to summarize available data concerning the relationship between HIV and HPV infection among women. The analysis comprises molecular mechanisms of HPV infection among HIV(+) women as well as HIV infection among HPV(+) women, prevalence of HPV and cervical lesions among women living with HIV and screening of HPV and cervical cancer (CC) among HIV infected women. Material and methods: The review includes publications from 2011 to 2020. The data has been collected by the use of the PubMed, Ovid, Up-To-Date and WHO website. Key words used to search for references include: HPV, HIV, prevalence, molecular mechanism, screening. Results: HIV infection is a risk factor for HPV acquisition. On the one hand, prevalence of HPV, multiple HPV, high risk HPV (hrHPV) infections and cervical intraepithelial neoplasia (CIN) is higher among HIV(+) women. On the other hand, HPV infection can also predispose to HIV acquisition. Evidence on how these viruses influence each other can be a breakthrough in the range of prevention, detection and treatment of both HIV and HPV infection. Conclusions: Relationship between HPV and HIV is an interest of nowadays medicine. Possibly, these viruses may cooperate and enable infection of each other. It has been showed that the prevalence of HPV, multiple HPV, hrHPV infections and cervical lesions is higher among HIV(+) in comparison to HIV(-) women. Further studies should be performed providing an insight into a molecular mechanism responsible for this cooperation.